Analysis of Factors Influencing Rice Farming Production in Sawangan, Magelang Regency - Eka Nur Jannah; Fatkhiyah Rohmah; Reismaya Wanamertan Nugroho; Zulaikha Anugraheni (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2026)
Sawangan District is a rice-producing area in Magelang Regency. The majority of its population relies on agriculture due to the region's significant agricultural potential. However, farmers face numerous challenges in rice production, including environmental, social, economic, and technological factors. This study aims to determine the factors influencing rice production by using a participatory approach that involves farmers in discussions during data collection. The method used in this study is descriptive quantitative, utilizing primary and secondary data. Data were processed using SPSS 16.0 software. The results of this study indicate that land area and seed quantity significantly influence rice production. Land area is the main determinant of rice production. According to classical production theory, land area is directly proportional to production. Meanwhile, seeds show a negative relationship with production: increasing the number of seeds planted leads to a higher seed density, resulting in suboptimal rice growth due to competition for nutrients, light, and root space. Other variables, namely age, education, number of workers, and amount of manure, do not significantly influence rice production. The results of this study are expected to inform policymakers in optimizing land use to increase productivity and determining the right number of seeds to achieve optimal production.